A case report of local precancer hyperkeratosis of red border of the low lip in a young patient - Larisa I. Glebova; Ekaterina V. Zadionchenko; Olga V. Kandalova (LLC "MEDIAFORMAT", 2022)
The red border of the lips is a special anatomical formation located on the border of the skin and the oral mucosa. Being a "transitional zone", it has its own morphological and functional features. There are no salivary glands on the red border of the lips, there are a small number of sebaceous glands, which contribute to the drying of the surface. This can lead to the formation of microtrauma. Concomitant diseases, deficiency of vitamins of groups A, B can lead to a violation of the protective properties and deterioration of regeneration. With age, the thickness of the lips decreases significantly. In addition, this zone is quite actively exposed to various irritating and traumatic factors that contribute to the development of chronic inflammatory processes. With the prolonged existence of the inflammatory process on the lips, the development of foci of malignancy is possible. There are a number of nosologies that most often lead to tissue degeneration. Currently, the frequency of malignant lesions of the lips has greatly increased. Precancerous diseases of the red border of the lips require special attention from specialists working with this area to prevent serious consequences. The article describes a case of development of obligate precancer of the red border of the lips in a young patient. The clinical features of limited precancerous hyperkeratosis are analyzed, a differential diagnosis is given, methods of diagnosis and treatment are described.